A comparative study DC-DC power converter between boost converter and series parallel-loaded resonant converter (S-PRC) for micro-fuel cells / Mohd Suhaizil Yaakop - Yaakop, Mohd Suhaizil (2010)
Micro-Fuel cells (u-FCs) are an emerging technology that has attracted lots of attention and research efforts. The fuels used are cheap and abundant, and the fast recharging mechanism makes u-FCs attractive replacements to many of today's energy sources. This project is aimed to compare two power converters namely Boost Converter and Series Parallel-Loaded Resonant Converter (S-PRC) for n-FCs that would provide a more efficient power source for consumer electronics. The design is challenging given the low input voltage from a single u-FC and its load dependent voltage characteristics on Cell Phone. The theoretical design is compared with the detailed simulation of both power converters carried out using PSIM Simulation software. Beside that, the value of the parameters will also influence the maximum performance of the system. MATLAB software is also used to produce the Voltage Conversion Ratio plot for S-PRC design. The results of both power converter designs are compared to demonstrate the difference based on the control type, component count & size. The analysis of the both power converters operating in the opened loop operation was analyzed under the steady state conditions.